2000
DOI: 10.1097/00008469-200012000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Stomach cancer history in the siblings of patients with gastric carcinoma

Abstract: A case-control study in the population of the Eastern Black Sea region of Turkey was conducted to learn the incidence of stomach cancer in the siblings of patients with gastric carcinoma. Among 1240 patients with gastric carcinoma, 168 had sibling(s) with a history of stomach cancer versus 19 cases in the control group matched according to age and gender (OR 10.07, P < 0.0001). The frequency of a history of stomach cancers and cancer of other organs in first- to third-degree relatives was 60.7% and 38.0%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
4
21
0
1
Order By: Relevance
“…All but three of the studies were published in English, one in Spanish and one was in Korean. The results of one of the included studies were published separately for siblings and parents[12,13] and one publication included two different studies on hospital- and community-based populations[14]. The primary objective of seventeen studies was to estimate the risk of gastric cancer in relatives of patients.…”
Section: Resultsmentioning
confidence: 99%
“…All but three of the studies were published in English, one in Spanish and one was in Korean. The results of one of the included studies were published separately for siblings and parents[12,13] and one publication included two different studies on hospital- and community-based populations[14]. The primary objective of seventeen studies was to estimate the risk of gastric cancer in relatives of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Having a first-degree relative with gastric cancer is a risk factor for gastric cancer with an OR varying from 2 to 10 in relation to geographic region and ethnicity [170]. A large study from Turkey reported an OR of 10.1 for siblings of gastric cancer patients, although these results were not adjusted for environmental factors [171]. Other European (OR 1.8-3.5), American (OR 2.2), and Asian (OR 1.5-9.9) case-control studies consistently provided corroboration that having a family history of gastric cancer is a risk factor [172][173][174][175][176][177][178][179].…”
Section: Biopsy Samplingmentioning
confidence: 99%
“…In these studies, the odds ratios (OR) of gastric cancer were calculated with reference to one or more first-or second-degree relatives with gastric cancer, but the definition of a positive family history varied between studies. Most studies combined all first-degree relatives (i.e., siblings and parents) but one study published results separately for siblings and parents (Bakir et al, 2000(Bakir et al, , 2003. Dhillon et al (2001) studied 695 cases and 629 population-based controls from the United States and estimated the familial relative risk for gastric cancer to be 2.2 (95% CI 1.5 -3.3).…”
Section: Worldwide Distribution Of Gastric Cancermentioning
confidence: 99%
“…In the large Turkish study, the results for siblings were published in 2000 (see Bakir et al, 2000) and the results for parents were published in 2003 (see Bakir et al, 2003). This large study included 1240 cases of gastric cancer and 1240 hospitalbased non-cancer controls.…”
Section: Worldwide Distribution Of Gastric Cancermentioning
confidence: 99%